Recent Developments in Mouse Trauma Research Models: A Mini-Review - Gihring, Adrian; Gärtner, Fabian; Schirmer, Melanie; Wabitsch, Martin; Knippschild, Uwe (Frontiers in Physiology, 2022)
The urgency to investigate trauma in a controlled and reproducible environment rises since multiple trauma still account for the most deaths for people under the age of 45. The most common multiple trauma include head as well as blunt thorax trauma along with fractures. However, these trauma remain difficult to treat, partially because the molecular mechanisms that trigger the immediate immune response are not fully elucidated. To illuminate these mechanisms, investigators have used animal models, primarily mice as research subjects. This mini review aims to 1) emphasize the importance of the development of clinically relevant murine trauma research, 2) highlight and discuss the existing conflict between simulating clinically relevant situations and elucidating molecular mechanisms, 3) describe the advantages and disadvantages of established mouse trauma models developed to simulate clinically relevant situations, 4) summarize and list established mouse models in the field of trauma research developed to simulate clinically relevant situations.